Prevention of Abuse of Authority, An Analysis of Integrity at Class IIA Sragen Correctional Facility and Class I Surakarta Detention Center: Pencegahan Penyalahgunaan Wewenang, Suatu Analisis Integritas Di Lapas Kelas IIA Sragen dan Rutan Kelas I Surakarta - Atmaja, Satrio Surya; Pangestuti, Naniek (Universitas Muhammadiyah Sidoarjo, 2025)
Abuse of authority in correctional institutions is a problem that can threaten the legitimacy of public administration. This study investigates the application of integrity as a mechanism to prevent abuse of authority in Technical Implementation Units for Corrections, namely the Class IIA Correctional Institution in Sragen and the Class I Detention Center in Surakarta. Using qualitative descriptive methods and the six-dimensional integrity framework proposed by Leo Huberts (2014), this study explores key components including system integrity, moral virtue, accountability, openness, rule enforcement, and exemplary behavior. Data were collected through interviews, observation, and documentation. The results of the study show that integrity at the Sragen Class IIB Prison is based on formal work rules and implementation by Satops Patnal, reinforcement in assembly forums, reinforcement of religious values, monthly reports, participatory facilities, and role models for officers. Meanwhile, what is different at the Surakarta Class I Detention Center is the existence of body checks on employees, checks on employees' belongings, and reviews of conditions. Integrity fosters a work culture that not only prevents violations through rules and sanctions, but also maintains ethical behavior through religious guidance, moral examples, and participatory monitoring. This study emphasizes that institutional integrity must be cultivated as a shared organizational value rather than a reactive response to violations. By instilling integrity across all operational, behavioral, and cultural dimensions, correctional institutions can create a robust system that minimizes opportunities for abuse of authority.